RELATIONSHIP BETWEEN LEVEL OF SERUM ADIPONECTIN AND FRAILTY IN ELDERLY PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Marfiani, Erika; Ichwani, Jusri; Widajanti, Novira; Maranatha, Daniel; Amin, Muhammad (Indonesian Journal of Tropical and Infectious Disease, 2020)
Elderly are especially prone to the adverse health effects of chronic obstructive pulmonary disease (COPD). COPD is a typical aging disease which is found to be about 12% in the age group more than 64 years old. Frailty is an important geriatics syndrome, while adiponectin is an important adipokine that regulate homeostasis of energy. Adiponectin is affected by age, especially in males. Adiponectin levels increases as subcutaneous fat cells in older men decreases. Increased adiponectin can lead to muscle wasting which will further reduce body weight and body mass index (BMI), which indirectly also increases the degree of frailty. Until now the relationship between adiponectin with frailty degree in advanced COPD is still unknown.The aims of this study was to investigate the relationship between plasma adiponectin level and frailty in COPD elders. This was an observational analytic cross-sectional study. All anthropometric parameters, including weight, height, and body mass index (BMI), were measured. Adiponectin was measured by ELISA methods obtained from venous blood samples. Aged more than or equal to 60 years old, the patients underwent spirometry to determine the degree of airflow limitation and the degree of frailty defined by the Fried criteria. Statistic analysis used Rank Spearman. Thirty-eight male COPD patients became the subject of the study. The average age was 70-74 years, with a total of 13 robust, 12 prefrails and 13 frail patients. Level of adiponectin (mean and SD) in robust, prefrail, and frail were 6.84+ 2.66 , 6.58 + 4.27, and 11.62 + 4.90 respectively, p=0.015. Further analysis showed that level of adiponectin rose progresively with an increasing number of components of frailty. The degree of obstruction mostly with mild (42.1%), and no subjects with very severe. There were an increase in serum adiponectin levels in all subjects. In conclusion, level of adiponectin serum correlates positively with the degree of frailty.